Deadlock verification of a DPS coordination strategy and its alternative model in pi-calculus. (1st January 2012) - Robles-Granda, Pablo D.; Khorasani, Elham S.; Rahimi, Shahram; Carver, Norman
A key issue for distributed problem solving (DPS) systems is coordination of the agent's actions, and methods for producing effective coordination strategies remain an active area of research. Because there are not yet approaches that can automatically produce such strategies, some human engineering is often still necessary. As a result, there is a need for a formal tool to support such human engineering. In a previous work (Khorasani et al., 2009), we investigated the use of pi-calculus as a formal language for modelling DPS coordination strategies and showed how such models could be used to evaluate the time performance of a strategy. In this paper, we focus on verification of coordination strategies. More specifically, we utilise the formal semantics of pi-calculus to detect deadlocks in a coordination strategy. We also show how, by imposing certain constraints on the pi-calculus model, one would be able to design a deadlock-free coordination strategy.